Chitosan film as recyclable adsorbent membrane to remove/recover hazardous pharmaceutical pollutants from water: the case of the emerging pollutant Furosemide. Issue 2 (24th November 2020) - Rizzi, Vito; Gubitosa, Jennifer; Fini, Paola; Romita, Roberto; Nuzzo, Sergio; Gabaldón, José Antonio; Gorbe, María Isabel Fortea; Gómez-Morte, Teresa; Cosma, Pinalysa
Abstract: Due to the negative effects of emerging contaminants on the environment, that can potentially induce deleterious effects in aquatic and human life, this paper focuses on the removal from the water of Furosemide, through the adsorption process. Indeed, only a few papers are available in the literature about the Furosemide adsorption and, chitosan films are thus proposed for this purpose as safe, sustainable, and recyclable adsorbent materials. In the present work, the effects on the adsorption process of several experimental parameters such as the pH values, ionic strength, amount of adsorbent/pollutant, and temperature values were investigated. The kinetics models, isotherms of adsorption, and the thermodynamic parameters were studied showing that the Furosemide physisorption occurred on the heterogeneous Chitosan surface, endothermically (Δ H ° = +31.27 ± 3.40 kJ mol −1 ) and spontaneously (Δ S ° = +150.00 ± 10.00 J mol −1 K −1 ), following a pseudo-second-order kinetic model. The 90% of the pollutant was adsorbed in 2 h, with a maximum adsorption capacity of 3.5 mg × g −1 . Despite these relatively low adsorption capacities, experiments of desorption were performed and 100% of adsorbed Furosemide was recovered by using concentrated NaCl solutions, proposing a low-cost and green approach, with respect to the previous literature relative to the Furosemide adsorption, fundamental for the pollutant recovery and adsorbent reuse.